Absorption burst in the solar sporadic radio emission at 10−30 MHz frequencies - Konovalenko, A.A.; Stanislavsky, A.A.; Abranin, E.P.; Dorovsky, V.V.; Mel'nik, V.N. (Кинематика и физика небесных тел, 2005)
We report the results of UTR-2 radio telescope observations of an absorption burst at the decameter range. This event is associated with two consecutive M-class flares and happened after the second M-flare. The latter flare was accompanied by Type II, Type IV radio sweeps and a CME. The observed bandwidth of the burst is about 20 MHz. The size of the absorption region is compared with the solar radius. The frequency drift rate of the absorption burst is about −0.12 MHz/s. The features of this event are discussed.